Evaluation of a Clinical Index as a Predictive Tool for Primary Ciliary Dyskinesia - Martinů, Vendula; Bořek-Dohalská, Lucie; Varényiová, Žofia; Uhlík, Jiří; Čapek, Václav; Pohunek, Petr; Koucký, Václav (Diagnostics (Basel, Switzerland), 2021)
BACKGROUND: In primary ciliary dyskinesia (PCD) there is no single diagnostic test. Different predictive tools have been proposed to guide referral of high-risk patients for further diagnostic workup. We aimed to test clinical index (CI) on a large unselected cohort and compare its characteristics with other widely used tools-PICADAR and NA-CDCF. METHODS: CI, PICADAR, and NA-CDCF scores were calculated in 1401 patients with suspected PCD referred to our center. Their predictive characteristics were analyzed using receiver operating characteristics (ROC) curves and compared to each other. Nasal nitric oxide (nNO) was measured in 569 patients older than 3 years. RESULTS: PCD was diagnosed in 67 (4.8%) patients. CI, PICADAR, and NA-CDCF scores were higher in PCD than in nonPCD group (all p < 0.001). The area under the ROC curve (AUC) for CI was larger than for NA-CDCF (p = 0.005); AUCPICADAR and AUCNA-CDCF did not differ (p = 0.093). An overlap in signs and symptoms among tools was identified. PICADAR could not be assessed in 86 (6.1%) patients without chronic wet cough. For CI laterality or congenital heart defects assessment was not necessary. nNO further improved predictive power of all three tools. CONCLUSION: CI is a feasible predictive tool for PCD that may outperform PICADAR and NA-CFCD.
Keywords: North America criteria defined clinical features (NA-CDCF); predictive tools; nasal nitric oxide (nNO); primary ciliary dyskinesia rule (PICADAR); clinical index (CI); primary ciliary dyskinesia (PCD)